Analisis Self Efficacy Siswa SMK Terhadap Pencapaian Kemampuan Koneksi Matematis - Nuary, Rusdi Hamdany; Triyono, Ageng; Permatasari, Nisa (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The aim of the research is to describe students' mathematical connection abilities in terms of self-efficacy. The objectives were achieved through descriptive research with a qualitative approach. The research subjects involved were 10 students of class AK 1 at SMKN 1 Cikarang Utara. The instruments for collecting data are mathematical connection test questions, self-efficacy questionnaires, and interview guides. The score of the test results is calculated and analyzed based on the level of achievement of the mathematical connection indicators. The percentage of questionnaire results was calculated based on self-efficacy indicators and analyzed based on categorization. Interview data is used to strengthen conclusions regarding whether there is a relationship between students' mathematical connection abilities and their self-efficacy. The results of data analysis show that the achievement of students' mathematical connection ability indicators is still relatively low, as shown by the achievement of the connection indicator with other scientific disciplines of only 31% and the connection indicator with daily life of only 0.69%. This low achievement is caused by the condition of students' self-efficacy which is categorized as poor at the strength level and not good at the magnitude and generality levels